2014
DOI: 10.1007/s11606-014-2895-9
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Approaches for Engaging Patients for Research on Rare Diseases

Abstract: BACKGROUND: Patients with rare diseases have limited access to useful information to guide treatment decisions. Engagement of patients and other stakeholders in clinical research may help to ensure that research efforts in rare diseases address relevant clinical questions and patient-centered health outcomes. Rare disease organizations may provide an effective means to facilitate patient engagement in research. However, the effectiveness of patient-engagement approaches, particularly for the study of rare dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(150 citation statements)
references
References 33 publications
(116 reference statements)
3
144
0
2
Order By: Relevance
“…However, it is arguably more critical within a team in which people may not have worked together before and may be bringing different expectations about how work ought to proceed. 9. Think carefully about labels, as they convey implicit values.…”
Section: Theme 3: Facilitating Good Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is arguably more critical within a team in which people may not have worked together before and may be bringing different expectations about how work ought to proceed. 9. Think carefully about labels, as they convey implicit values.…”
Section: Theme 3: Facilitating Good Communicationmentioning
confidence: 99%
“…8 Third, benefits of partnership may be difficult to formally assess. 9 Fourth, time requirements are a frequent concern for everyone. 7,10 These reviews offer valuable evidence syntheses relevant to partnership, as do recommendations from long-standing traditions of methods such as community-based participatory research 11 and participatory action research.…”
Section: Introductionmentioning
confidence: 99%
“…The effective engagement of patients in research on rare diseases is currently an area of increasing interest [8, 20]. This has come about as a result of governments giving greater priority and incentives for rare disease research, including through orphan drug legislation, [21, 22] and promotion by policy makers [20, 23].…”
Section: Discussionmentioning
confidence: 99%
“…This has come about as a result of governments giving greater priority and incentives for rare disease research, including through orphan drug legislation, [21, 22] and promotion by policy makers [20, 23]. This has occurred in parallel with a recent shift from a passive role for patients in research towards a desire to play a more involved role in the research process, as demonstrated by the survey outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In general, PE offers an opportunity to improve the science of PRO measure development, and to reinforce the patient centeredness of the process [44,45]. For example, PE may facilitate identification of topics/areas for future research, development of optimal study design, selection of appropriate outcomes/domains to include in a PRO instrument, and clarification of patients' description of symptoms.…”
Section: Patient Engagementmentioning
confidence: 99%